Description of a new species of Pareiorhina (Siluriformes: Neoplecostominae) from Rio Sao Francisco basin - Roxo, Fabio Fernandes [UNESP]; Da Costa E Silva, Gabriel de Souza; Mehanna, Mahmoud [UNESP]; Oliveira, Claudio [UNESP] (Magnolia Press, 2012)
A new species of Pareiorhina (Neoplecostominae) from the Rio Sao Francisco basin, Minas Gerais State, Brazil, is described. The new species is distinguished from its congeners (Pareiorhina brachyrhyncha, P. carrancas, and P. rudolphi) by traits related to small plates covered with odontodes randomly distributed on the abdomen, minute lateral cusps on the teeth, pointed odontodes covering pectoral, pelvic, and anal-fin first rays, caudal-fin being completely dark with one hyaline bar, absence of a ridge on the postdorsal surface of trunk, shape of premaxillae and dentaries, and by the absence of odontodes at the ventral tip of the snout.
Keywords: cascudinhos; catfish; freshwater; Loricariidae; Neotropical region; South America